Submaxillary gland androgen-regulated protein 3A expression is an unfavorable risk factor for the survival of oropharyngeal squamous cell carcinoma patients after surgery - Grünow, Jennifer; Holzinger, Dana; Acuña Sanhueza, Gustavo A.; Flechtenmacher, Christa; Plath, Karim; Lahrmann, Bernd; Grabe, Niels; Plinkert, Peter K.; Heß, Jochen (European archives of oto-rhino-laryngology and head & neck, 2013)
Recently, increased expression of the submaxillary gland androgen-regulated protein 3A (SMR3A) was found in recurrent tumors of an orthotopic floor-of-mouth mouse tumor model after surgery. However, SMR3A expression in the pathogenesis of human malignancy and its correlation with the clinical outcome have not been addressed so far. We analyzed tissue microarrays with specimens from oropharyngeal squamous cell carcinoma (OPSCC) patients (n = 157) by immunohistochemistry and compared SMR3A expression with clinical and pathological features by statistical analysis. Strong SMR3A expression was found in almost 36 % of all primary OPSCCs. Although, SMR3A protein levels were not associated with any clinical or histopathological feature tested, univariate Kaplan-Meier analysis revealed a significant correlation between high SMR3A protein expression and poor progression-free (p = 0.02) and overall survival (p = 0.03). Furthermore, high SMR3A expression was an independent marker for poor clinical outcome [HR (SMR3Ahigh vs. SMR3low) = 2.32; 95 % CI = 1.03-5.23] concerning overall survival in a multivariate analysis of OPSCC patients with surgery as primary therapy (n = 100). Our data demonstrate for the first time increased SMR3A protein expression in the pathogenesis of OPSCC, which serves as an unfavorable risk factor for patient survival.